Pengaruh Pemberian Mikoriza Glomus sp., Trichoderma harzianum dan Pupuk Hayati Terhadap Pertumbuhan dan Produksi Tanaman Jagung (Zea mays L.) - Tiara Primayanti; Tini Surtiningsih; Thin Soedarti; Sucipto Hariyanto (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
The aim of this study was to evaluate the impact of mycorrhizal applications of Glomus sp., Trichoderma harzianum species, and organic biofertilizers on the growth parameters and productivity of corn (Zea mays L.). This experiment was conducted in the period of May-July 2012 on agricultural land located in Kendal Village, Kendal District, Ngawi Regency. The applied methodology was a completely randomized design (CRD) with four treatment groups; (1) the control group, (2) the Glomus sp. mycorrhiza group as much as 30 g/plant, (3) the T. harzianum group as much as 30 ml/plant, (4) the biological fertilizer group as much as 5 ml/plant with each treatment repeated five times. Data related to plant growth and production were analyzed using the Analysis of Variance (ANOVA) test, with the Duncan test at a significance 5% to determine significant differences between treatments.. The results from the four treatments show that the application of Glomus sp., T. harzianum, and organic biofertilizers have a significant effect (α < 0.05) on the growth and yield of corn. T. harzianum treatment produced the highest plant height, which was 181 ± 8.9 cm, while the application of Glomus sp. mycorrhiza gave the best contribution to root length parameters with an average of 41.2 ± 5.3 cm. The application of biofertilizer also provides an optimum result for corn weight of 144 ± 28.9 g